Construction of an Index System of the Biosafety Incident Response Capability for Nursing Staff: A Delphi Study - Chao Wu; Mengyi Hu; Xinyan Zhang; Mimi Fu; Lu Li; Qiang Xu; Xiaolan Guo; Hongjuan Lang (Nursing Open, 2025)
ABSTRACT Aim This study was to establish a scientific and sensitive index system of the biosafety incident response competence for clinical nursing staff to provide a reference for the evaluation of nurses' biosafety incident response competence. Design A modified recommendation for the conducting and reporting of Delphi studies was used to guide this study. Methods According to the literature review, preliminary biosafety incident response competence indicators for nursing staff were established, and an expert survey questionnaire was designed. The evaluation system for clinical nurses' biosafety incident response competence indicators was determined using the Delphi method. Results After two‐round Delphi survey, 28 nursing specialists from six provinces and cities around China, with expertise in three prevention research, epidemiology, military health service and biosafety incident rescue, established the index system of the biosafety incident response competence for nursing staff from April to May 2023. The final index system of the biosafety incident response competence was composed of four primary indicators, namely, biosafety incident preparedness, monitoring competence, protection ability and nursing disposal abilities; 10 secondary indicators and 49 tertiary indicators. The effective recovery rates of the two rounds of expert survey questionnaires were 93.33% and 100%, respectively. The authority coefficient, judgement coefficient and familiarity degree of Delphi experts were 0.877, 0.911 and 0.843, respectively. The Kendall's harmony coefficients of the two rounds of expert consultation were 0.301–0.384 and 0.401–0.424, respectively, with statistical significance (p < 0.05). Conclusion The index system of the biosafety incident response competence for nursing staff is scientific and reliable. The authors have provided a more reliable and comprehensive basis for evaluating nurses' biosafety incident response competence in the future. Conclusion and Implications for Nursing It is helpful for nursing staff to perform better in biosafety incident by clarifying the specific items of biosafety response competence. Nursing staff can use the index system as the evaluation tool and training references to enhance their biosafety incident response competence. Patient or Public Contribution No patient or public contribution.